A Survey Assessment of Sun Exposure Safety Behaviors and Knowledge Among Adults Living in Yemen and the United States - Algutaini, Safana Abdullah (Journal of Medical Health Research and Psychiatry, 2024)
Sun exposure poses significant health risks, including skin cancer and cataracts, particularly in regions with high UV radiation levels. Therefore, this study aims to assess and compare sun exposure safety behaviors and knowledge among adults in Yemen and the United States. An online questionnaire was administered to gather data on participants' sun protection habits, knowledge of sun protection factors, and awareness of the risks associated with sun exposure. The results revealed notable differences between the two regions. While adults in the United States demonstrated higher levels of sun protection behaviors, such as regular use of sunscreen and protective clothing, participants in Yemen exhibited lower levels of sun protection knowledge and practices. Cultural and religious practices in Yemen, which often involve modest clothing that covers much of the skin, were found to influence sun protection behaviors. These findings underscore the need for culturally tailored public health campaigns to enhance sun protection behaviors and knowledge in both regions. By addressing regional differences and cultural contexts, targeted interventions can be developed to reduce sun-related health risks and promote safer sun exposure practices.